The Apalachicola Barrier Island complex: a benchmark for MIS 5e (125 ka) sea-level oscillations? - Nikos Georgiou; Alexander R. Simms; Roger C. Creel; Silas Dean; Denovan Chauveau; Ciro Cerrone; Claudia Caporizzo; Alessio Rovere (Geomorphology, 2026)

From Ice to Isolation: A geochemical reconstruction of the palaeoenvironmental evolution of Gairloch, NW Scotland (UK), since the Last Glacial Maximum - Jennifer Taylor; David Selby; Jeremy M. Lloyd; Louise Best; Luca Podrecca; Bradley B. Sageman; Alexander R. Simms (Journal of Quaternary Science, 2026)
Complex relative sea‐level (RSL) changes are associated with the deglaciation of the British and Irish Ice Sheet (BIIS). Sediment archives from Loch Bad na h‐Achlaise, an isolation basin in NW Scotland, UK, span Late Glacial to Holocene time and record sea‐level change and ice proximity via a geochemical and biostratigraphic multiproxy approach. Osmium and carbon isotope, carbon and nitrogen content, and X‐ray fluorescence (XRF) data suggest that the basal sedimentary unit reflects a glaciomarine depositional setting, a finding previously unresolved due to an inadequate biostratigraphic framework. The 187 Os/ 188 Os record from the basin captures the RSL history of this site and illustrates the interplay between the local signal of glacial isostatic adjustment and the non‐local signal of glacio‐eustatic sea‐level rise. By coupling the 187 Os/ 188 Os data with a detailed age–depth model, our study demonstrates a period of RSL fall between 16.2 and 15.9 cal ka BP, which culminates in basin isolation. The close agreement between the biostratigraphy, where available, and the 187 Os/ 188 Os record confirms the viability of this isotope system as an RSL proxy not reliant on microfossil preservation and thus a potentially effective approach when poor microfossil preservation hampers palaeoenvironmental reconstruction.

New RSL constraints for the Minch from OSL-dated Lateglacial shorelines - Emily Huffman; Alexander R. Simms; Tom Bradwell; Louise Best; Jeremy M. Lloyd; Sarah L. Bradley; Regina DeWitt (Quaternary Science Reviews, 2025)

Reconstructing Late Pleistocene relative sea levels on transgressed shelves: an example from central California - Elisa Medri; Alexander R. Simms; Jared Kluesner; Samuel Y. Johnson; Stuart P. Nishenko; H. Gary Greene; James E. Conrad; Devin Rand (Quaternary Science Reviews, 2025)

Was Scotland covered by an ice sheet during Marine Isotope Stage 4? Insights from the pre‐Last Glacial Maximum marine terraces of northwest Scotland - Alexander R. Simms; Regina DeWitt; Sarah L. Bradley; Emily Huffman; Louise Best; Tom Bradwell; Jeremy M. Lloyd; Samuel B. Kachuck (Journal of Quaternary Science, 2025)
Raised shorelines provide important constraints on past sea levels, glacial isostatic adjustment (GIA), and rates and directions of vertical crustal motion. Although most raised shorelines across NW Scotland relate to post‐Last Glacial Maximum (LGM) glacial‐isostatic rebound, many undated shorelines lie above the marine limit established from isolation basins. Here, we present new optically stimulated luminescence (OSL) ages for a raised marine terrace at an elevation of 28 m in Slaggan Bay of NW Scotland. Four OSL ages suggest the feature is pre‐LGM, likely Marine Isotope Stage (MIS) 3. Global mean sea levels (GMSL) during MIS 3 are thought to have been ~40–60 m below present across most of the globe. We use a pair of GIA models to determine what ice sheet and sea‐level scenarios might provide an explanation for these anomalously high sea levels during MIS 3. Our results suggest that in the absence of tectonic activity, such high MIS 3 shorelines across NW Scotland require a MIS 4 ice sheet in Scotland, with postglacial rebound of the crustal depression following its demise during MIS 3 responsible for the elevated shoreline features at that time.

Insights into the sea-level history of the South Shetland Islands from ground penetrating radar on Livingston Island, Antarctica - Cameron Gernant; Alexander R. Simms; Regina DeWitt; Brittany Theilen; Christopher N. Garcia; Michael Goebel (Quaternary Science Reviews, 2025)

Late Pleistocene sea-level constraints across Antarctica - Alexander R. Simms; Takeshige Ishiwa; Dominic A. Hodgson; Toru Tamura; Regina DeWitt (Quaternary Science Reviews, 2024)

Constraining the radiocarbon reservoir age for the Southern Ocean using whale bones salvaged from early 20th century whaling stations - Claire Divola; Alexander R. Simms; Angela Sremba; C. Scott Baker; Ari Friedlaender; John Southon (Quaternary Science Reviews, 2024)

Subaqueous clinoforms created by sandy wave-supported gravity flows: Lessons from the Central California shelf - Elisa Medri; Alexander R. Simms; Jared Kluesner; Samuel Y. Johnson; Stuart P. Nishenko; H. Gary Greene; James E. Conrad (Marine Geology, 2023)

Circulating cell-free DNA in health and disease — the relationship to health behaviours, ageing phenotypes and metabolomics - Laura Kananen; Mikko Hurme; Alexander Bürkle; Maria Moreno-Villanueva; Jürgen Bernhardt; Florence Debacq-Chainiaux; Beatrix Grubeck-Loebenstein; Marco Malavolta; Andrea Basso; Francesco Piacenza; Sebastiano Collino; Efstathios S. Gonos; et al. (GeroScience, 2023)
Circulating cell-free DNA (cf-DNA) has emerged as a promising biomarker of ageing, tissue damage and cellular stress. However, less is known about health behaviours, ageing phenotypes and metabolic processes that lead to elevated cf-DNA levels. We sought to analyse the relationship of circulating cf-DNA level to age, sex, smoking, physical activity, vegetable consumption, ageing phenotypes (physical functioning, the number of diseases, frailty) and an extensive panel of biomarkers including blood and urine metabolites and inflammatory markers in three human cohorts (N = 5385; 17–82 years). The relationships were assessed using correlation statistics, and linear and penalised regressions (the Lasso), also stratified by sex. cf-DNA levels were significantly higher in men than in women, and especially in middle-aged men and women who smoke, and in older more frail individuals. Correlation statistics of biomarker data showed that cf-DNA level was higher with elevated inflammation (C-reactive protein, interleukin-6), and higher levels of homocysteine, and proportion of red blood cells and lower levels of ascorbic acid. Inflammation (C-reactive protein, glycoprotein acetylation), amino acids (isoleucine, leucine, tyrosine), and ketogenesis (3-hydroxybutyrate) were included in the cf-DNA level-related biomarker profiles in at least two of the cohorts. In conclusion, circulating cf-DNA level is different by sex, and related to health behaviour, health decline and metabolic processes common in health and disease. These results can inform future studies where epidemiological and biological pathways of cf-DNA are to be analysed in details, and for studies evaluating cf-DNA as a potential clinical marker.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Local and regional constraints on relative sea‐level changes in southern Isle of Skye, Scotland, since the Last Glacial Maximum - Louise Best; Alexander R. Simms; Martin Brader; Jerry Lloyd; Juliet Sefton; Ian Shennan (Journal of Quaternary Science, 2022)
New relative sea‐level (RSL) data constrain the timing and magnitude of RSL changes in the southern Isle of Skye following the Last Glacial Maximum (LGM). We identify a marine limit at ~ 23 m OD, indicating RSL ~20 m above present c . 15.1 ka. Isolation basin data, supported by terrestrial and marine limiting dates, record an RSL fall to 11.59 m above present by c . 14.2 ka. This RSL fall occurs across the time of global Meltwater Pulse 1A, supporting recent research on the sources of ice melting. Our new data also help to resolve some of the chronological issues within the existing Isle of Skye RSL record and provide details of the sub‐Arctic marine environment associated with the transition into Devensian Lateglacial climate at c . 14.5 k cal a bp , and the timing of changes in response to the Loch Lomond Stadial climate. Glacio‐isostatic adjustment (GIA) model predictions of RSL deviate from the RSL constraints and reflect uncertainties in local and global ice models used within the GIA models. An empirical RSL curve provides a target for future research.

Accumulation of glycated proteins suggesting premature ageing in lamin B receptor deficient mice - Frank Hause; Dietmar Schlote; Andreas Simm; Katrin Hoffmann; Alexander Navarrete Santos (Biogerontology, 2018)

Tectonic Subsidence of California Estuaries Increases Forecasts of Relative Sea-Level Rise - Alexander Simms; Laura C. Reynolds; Michael Bentz; Angela Roman; Thomas Rockwell; Robert Peters (Estuaries and Coasts, 2016)